Outcomes and predictors of relapse and severe pneumonia in Chinese patients with AQP4-IgG-positive neuromyelitis optica spectrum disorder receiving inebilizumab: a prospective cohort study - Huang, Wenjuan; Tan, Hongmei; ZhangBao, Jingzi; Wang, Liang; Fan, Yuxin; Wang, Zhouzhou; Zhao, Chongbo; Lu, Jiahong; Dong, Qiang; Zhou, Lei; Quan, Chao (Frontiers in Immunology, 2026)
BackgroundInebilizumab was included in China’s national reimbursement drug list in 2023, enhancing its accessibility. However, there is a paucity of real-world data evaluating its performance in Chinese patients with aquaporin-4 immunoglobulin G–seropositive neuromyelitis optica spectrum disorder (AQP4-IgG+ NMOSD). This prospective study therefore sought to assess the treatment outcomes and identify predictive factors for relapse and severe pneumonia in Chinese patients treated with Inebilizumab.MethodsThis study enrolled AQP4-IgG+ NMOSD patients receiving ≥1 dose of inebilizumab from March 2023 to June 2025. The primary outcome was time to first relapse. Secondary outcomes included annualized relapse rate (ARR), Expanded Disability Status Scale (EDSS) score, drug retention rates, and adverse events (AEs). Multivariate regression analyses were conducted to identify predictors of relapse and severe pneumonia.ResultsAmong 136 patients (91.9% female; mean age 40.3 years; median treatment duration 13.8 months), the 12-month relapse-free rate was 88.1% (95% confidence interval [CI] =82.1–94.5%). Thirteen patients experienced 14 relapses, with 7 occurring within the first 6 months. The median time to first relapse was 5.2 months (range, 0.3–11.8). Risk factors for relapse within 12 months included: age at onset ≤ 20 years (hazard ratio [HR] 8.17, 95% CI = 1.96–34.03, p=0.004), disease duration >5 years (HR 8.06, 95% CI = 1.72–37.83, p=0.008), and pre-treatment relapses (HR 3.04, 95% CI = 1.32–6.98, p=0.009). The annualized relapse rate (ARR) significantly decreased (1.496 vs 0.117, p<0.001). The median EDSS score decreased (from 2.5 to 2.0, p = 0.002) in patients who started inebilizumab during the remission phase. The 12-month drug retention rate was 88.9% (95% CI 82.8–95.5%). Seven patients developed severe pneumonia, significantly associated with baseline EDSS ≥6.5 (odds ratio [OR] 25.4, 95% CI = 2.12–334, p=0.013) and IgG <6 g/L (OR 14.2, 95% CI = 1.79–136, p=0.007).ConclusionThis study confirms the real-world effectiveness of inebilizumab in Chinese NMOSD patients but identifies distinct clinical profiles for relapse and infection risk. Patients with early-onset, long-standing, or highly active disease are at greater risk of breakthrough relapses, whereas those with high disability and hypogammaglobulinemia require vigilance for severe pneumonia. These findings advocate for a risk-stratified management approach to optimize treatment outcomes.